A phase 3, randomized, double-blind, clinical study to evaluate the long-term safety and efficacy of gefapixant in Japanese adult participants with refractory or unexplained chronic cough - Akio Niimi; Hironori Sagara; Masashi Kikuchi; Ichiro Arano; Asako Sato; Masayoshi Shirakawa; Carmen La Rosa; David Muccino (Allergology International, 2022)
Background: In two phase 3, global clinical trials (COUGH-1 and COUGH-2), the P2X3-receptor antagonist gefapixant significantly reduced objective 24-h cough frequency in participants with refractory or unexplained chronic cough (RCC or UCC) at a dosage of 45 mg twice daily (BID), with an acceptable safety profile. The primary objective of this phase 3, randomized, double-blind, parallel-group study was to assess the safety and tolerability of gefapixant in Japanese participants with RCC or UCC (ClinicalTrials.gov, NCT03696108; JAPIC-CTI, 184154). Methods: Participants aged ≥20 years with chronic cough lasting ≥4 months and a diagnosis of RCC or UCC despite treatment in accordance with Japanese Respiratory Society guidelines were randomized 1:1 to receive gefapixant 15 or 45 mg BID for 52 weeks. The primary objective was to evaluate the safety and tolerability of gefapixant, including adverse events (AEs) and discontinuations due to AEs. Cough-specific quality of life was assessed using the Leicester Cough Questionnaire as a secondary objective. Results: Of 169 randomized and treated participants, 63% were female and mean age was 58 years. Adverse events were reported by 79 (94%) and 82 (96%) participants in the 15- and 45-mg BID groups, respectively. Most treatment-related AEs were taste related. Discontinuations due to AEs occurred in 6 (7%) and 17 (20%) participants receiving gefapixant 15 or 45 mg BID, respectively. There were no serious treatment-related AEs or deaths. Leicester Cough Questionnaire total scores improved from baseline through Week 52. Conclusions: Gefapixant had an acceptable safety profile, with no serious treatment-related AEs in Japanese participants.